How reliable is secondary risk stratification with stimulated thyroglobulin in patients with differentiated thyroid carcinoma? - Lemb, J.; Hüfner, M.; Meller, B.; Homayounfar, K.; Sahlmann, C.; Meller, J. (Nuklearmedizin - NuclearMedicine, 2013)
Objective: Primary risk factors in patients with differentiated thyroid carcinoma (DTC) are well established. In our institution, secondary risk stratification has been performed with stimulated Thyroglobulin (sTg; TSH > 30 mIU/l) within six months after primary therapy since 2001. In this study, we evaluated the predictive value of sTg for long-term disease- free survival (DFS). Patients, methods: Data of 202 consecutive patients with DTC were analyzed retrospectively. Median follow-up time was 6.4 years (12 months to 16.2 years). Patients were staged according to Union International Contre le Cancer (UICC) criteria. Primary risk stratification was carried out according to European Thyroid Association criteria. Initially, 134 patients (66%) were classified as low-risk and 68 patients (34%) as high-risk. The influence of established risk factors and sTg on DFS was analyzed at three different time points, up to 36 months after initial therapy. Results: In total, 169 (84%) of all patients remained in complete remission after surgery followed by radioiodine-therapy. Six patients (3%) developed tumour recurrence after initial complete remission. Primary risk factors for persistent disease were male sex, follicular or oncocytic tumour, primary tumour > 4 cm in diameter, initial lymph node involvement, initial metastatic disease and microscopic or macroscopic residual tumor. sTg ≤ 0.3 ng/ml measured within six months after initial therapy was a highly significant predictor (p ≤ 0.001) for lasting DFS, 99% of patients with sTg ≤ 0.3 ng/ml were in complete remission 36 months after initial therapy. Conclusions: A stimulated Tg ≤ 0.3 ng/ml within six months after initial therapy is a reliable predictor for long-term disease- free survival independent of primary risk stratification.
Keywords: Differentiated thyroid carcinoma; follow-up; secondary risk stratification; stimulated thyroglobulin